PENGARUH PROMOSI PESAING, KETIDAKPUASAN DAN KEBUTUHAN MENCARI VARIASI TERHADAP PERALIHAN MEREK PROVIDER XYZ DI KOTA DENPASAR - Prasetyo, Pande Ketut Adi Yoga; Warmika, I Gde Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The increase in internet users in Indonesia is very rapid, the phenomenon of covid-19 is one of the causes of the increase in internet users in Indonesia. However, the increase in internet users in Indonesia is not in line with the increase in users of the XYZ provider. XYZ provider actually experienced a significant decrease in users in 2021, which was 3.4 percent (Databoks.Kotadata (2021).This research is a type of quantitative research with data collection techniques using questionnaires. The sample was determined using a non-probability sampling model with a purposive sampling technique. Purposive sampling with samples in this study totaling 100 respondents who were former users of the XYZ provider in Denpasar City for the last three years. The data analysis technique used was multiple linear regression analysis with the SPSS for Windows program.This study aims to explain the effect of competitors' promotions, dissatisfaction, and the need for variation on the XYZ provider brand switching in Denpasar City. The results showed that all hypotheses were accepted. Promotion of competitors, dissatisfaction, the need to look for variations partially or simultaneously have a positive and significant effect on brand switching.